A COMPARISON OF SOME METHODS FOR DETERMINATION OF POTENTIAL EVAPOTRANSPIRATION FOR ROGERM BASIN, MANGESH, KURDISTAN REGION OF IRAQ - ALI, HALIZ SALEEM MOHAMMED; HAJI, GHARIBA YOUSIF; SALIM, JIHAD I. (Journal of Duhok University, 2022)
Potential evapotranspiration is an important component of the hydrological cycle at various spatial scales that impacts the runoff quantity and the irrigation water requirements. Potential evapotranspiration is a projectile worker in the ecosystem of the operation of evapotranspiration. The aims of this is to find the most suitable method for calculating monthly potential evapotranspiration in Rogerm basin area by comparing several methods. The climatic data for the period 2012-2021 were used in the models to estimate the potential evapotranspiration. The performance index was applied by using statistical criteria including R2, RMSE, MBE, and MAPE were used to compare the FAO-56-PM into four temperature-based methods and four radiation-based methods of PET at Mangesh Agrometeorological station. The study found that the Hargraves method is the most accurate one compared with other